THEORETICAL STUDY OF CO2:N2 ADSORPTION IN FAUJASITE IMPREGNATED WITH MONOETHANOLAMINE - A. E. O. Lima (Brazilian Journal of Chemical Engineering, 2015)
AbstractMany efforts have been made to develop amine-based solid adsorbents for capture of CO2 by adsorption. Compared with the traditional process of absorption in aqueous solutions of amines, the adsorbents with amine immobilized in solids generally result in processes with lower capital and energy costs. The literature contains some experimental studies of CO2 adsorption in impregnated materials; however, few studies are devoted to the theoretical interpretation of this system in terms of CO2 capture for post-combustion (N2 mixture with a low partial pressure of CO2). Therefore, this study investigates the adsorption of a CO2:N2 mixture on zeolite NaX impregnated with monoethanolamine (MEA), using molecular simulation. A model of NaX impregnated with MEA was proposed and the adsorption of a 15:85 (CO2:N2) mixture was investigated based on the Monte Carlo method. The simulation of the MEA impregnated zeolite at 25 ˚C predicted higher CO2 selectivity and significant improvement in the heat of adsorption. Unfortunately, the adsorption heat improvement did not translate into corresponding increases in the amount of adsorbed CO2. Moreover, MEA concentrations higher than 12 wt% hindered the adsorption of CO2molecules. An explanation for the results in terms of occupied volumes and interaction energies is presented.